I Mae - Madrigal, Keshia; Quirós, Carolina; Campos, Marcia (Screenwriter); Carvajal, Natalia (Cinetel, 2011)
Gaby and Elena are two young Costa Rican university students with dreams, plans and living a hectic life with their respective partners. Both are invited to attend a picnic to celebrate the birthday of a friend of one of them. The coexistence will last until the night and will demonstrate the reality so complex and confusing that the youth of the country lives, where individualism, apathy and conformity abound. That long day, only one of them will make the right decision...--